Development of Safety Management System Learning Through MOOCS to Improve Mastery of Aviation Safety Concepts for Cadets - I Gusti Agung Ayu Mas Oka; Fitri Masito; Ade Irfansyah; Dian Anggraini Purwaningtyas; Zalzariana Adelia Pramono (Yayasan Keluarga Guru Mandiri, 2022)
This type of research is research and development. The design of the development model in this study uses the ADDIE step (Analysis, Design, Develop, Implementation, Evaluation). However, this article only discusses up to the analysis stage, namely to find out student needs for the development of Introduction to Safety Management System learning through MOOCs. The study was conducted in May-June 2022. The samples in this study were 146 Palembang Poltekbang students who took the Safety Management System course. Sampling is done by purposive sampling technique. The research instrument used was a closed questionnaire consisting of 20 positive statements which is a modification of the Likert Scale with 4 answer choices, namely strongly agree with a score of 4, agree with a score of 3, disagree with a score of 2 and strongly disagree with a score of 1. The results of this study indicate that student agrees to do learning development Introduction To Safety Management System through MOOCs to improve mastery of aviation safety concepts.